Sistem Informasi Manajemen Badan Usaha Milik Desa (BUMDes) - Al Iqbal Bin Salim; Lillyan Hadjaratie; Salahudin Olii (Gorontalo State University, 2021)
The Village-Owned Enterprises (BUMDes) is managed separately from Village Government organization and is selected by village community through certain discussion. The management of such enterprises requires function of management support to be more efficient. The research aims to develop Management Information System of Village-Owned Enterprise to help manage it. This research employs descriptive method with prototyping method for the system development. The final result of this research is a Management Information System of Village-Owned Enterprises.